LPS-induced Airway-centered Inflammation Leading to BOS-like Airway Remodeling Distinct From RAS-like Fibrosis in Rat Lung Transplantation. Issue 6 (June 2020) - Takahagi, Akihiro; Sato, Masaaki; Chen-Yoshikawa, Toyofumi F.; Miyamoto, Ei; Saito, Masao; Gochi, Fumiaki; Hamaji, Masatsugu; Yoshizawa, Akihiko; Terasaki, Yasuhiro; Urushiyama, Hirokazu; Aoyama, Akihiro; Sonobe, Makoto; et al.
Abstract : Background: Localization of inflammatory stimuli may direct lung allografts to different phenotypes of chronic dysfunction, such as bronchiolitis obliterans syndrome (BOS) or restrictive allograft syndrome (RAS). We hypothesized that airway stimulation with lipopolysaccharide (LPS) in rats leads to airway-centered inflammation similar to human BOS. Methods: Rat left lung transplantation was conducted (donor: Brown Norway, recipient: Lewis). Allotransplant recipients received cyclosporine A (CsA) until postoperative day 56 with airway instillation of LPS (Allo-LPS, n = 8), phosphate buffered saline (Allo-PBS, n = 5) from days 35 to 46 (3 times a wk), or no further treatment (n = 4). Some allotransplant recipients received CsA until day 14 and were immunosuppression free after day 15 until day 56. Bronchial and pleural fibrosis were semiquantified; alveolar fibrosis was evaluated with a histological scale. Results: The Allo-LPS group had significantly increased International Society for Heart and Lung Transplantation rejection grades (grade A, P = 0.005; grade B, P = 0.004), bronchial obstructive proportion (0.34 ± 0.04% [Allo-LPS] versus 0.11 ± 0.04% [Allo-PBS], P = 0.006), and airway resistance (3.05 ± 1.78 cm H2 O·s/mL [Allo-LPS] versus 0.83 ± 0.58 cm H2 O·s/mL [Allo-PBS], P = 0.007) compared with other groups. Allotransplant recipients that underwent a short course of CsA developed RAS-like fibrosis involving the airways, alveoli, and pleura. Conclusions: Airway instillation of LPS in allografts under immunosuppression resulted in BOS-like airway-centered inflammation and fibrosis distinct from RAS-like diffuse fibrosis, which was induced by a shortened course of immunosuppression. We propose novel animal models for BOS and RAS after lung transplantation. Abstract : Supplemental Digital Content is available in the text.